2016
DOI: 10.1371/journal.pone.0160797
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of Diabetes Mellitus and Obesity and the Overlap of Comorbidities in HIV+ Hispanics Initiating Antiretroviral Therapy

Abstract: BackgroundCardiovascular disease (CVD) is a leading health threat for HIV+ patients on antiretroviral therapy (ART); cardiometabolic comorbidities are key predictors of risk. Data are limited on incidence of metabolic comorbidities in HIV+ individuals initiating ART in low and middle income countries (LMICs), particularly for Hispanics. We examined incidence of diabetes and obesity in a prospective cohort of those initiating ART in the Dominican Republic.MethodsParticipants ≥18 years, initiating ART <90 days p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 45 publications
0
9
1
Order By: Relevance
“…[1][2][3] Among individuals on suppressive ART, wasting has become less common and recent studies from both upper-and lower-income countries report weight gain irrespective of ART type. [4][5][6][7][8] Additionally, many countries have reported an increasing prevalence of overweight and obese states in HIV-infected persons even prior to ART initiation, consistent with trends in the general population. 6,9 As obesity rates rise, so does the risk for obesity-related complications.…”
Section: Introductionmentioning
confidence: 82%
“…[1][2][3] Among individuals on suppressive ART, wasting has become less common and recent studies from both upper-and lower-income countries report weight gain irrespective of ART type. [4][5][6][7][8] Additionally, many countries have reported an increasing prevalence of overweight and obese states in HIV-infected persons even prior to ART initiation, consistent with trends in the general population. 6,9 As obesity rates rise, so does the risk for obesity-related complications.…”
Section: Introductionmentioning
confidence: 82%
“…[ 6 , 15 , 16 ] As in the general population, overweight and obesity are associated with a number of detrimental health conditions in HIV-infected patients, including cardiovascular diseases and diabetes. [ 16 20 ] This study confirms that the prevalence of diabetes and cardiovascular disease is high in HIV-infected patients, and that overweight and obesity increasing in this population add excess risk of these comorbidities. BMI distribution of patients starting cART is similar to that of the general population, but there is a significant risk of BMI gain during the first years after cART initiation.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, HIV patients with high with CD4 counts receiving antiretroviral treatment displayed marked increases in body mass index, overweight/obesity, and central obesity among patients but not those with higher CD4 counts, implying that obesity risk was exacerbated by lower CD4 counts [63]. It is worth noting that in the Hispanic cohort (above) of HIV patients receiving antiviral therapy the incidence of obesity/overweight was similar to that witnessed in high income countries with the expected accompanying risks [61]. Further, Obesity linked to commonplace among HIV-infected Nigerians maintaining antiretroviral therapy [64].…”
Section: Volume 1 • Issue 2 • 1000113mentioning
confidence: 99%
“…Price et al [60] have obtained a tendency towards an increasing prevalence of metabolic syndrome and elevated risk for cardiovascular disorders among HIV patients in spite of the ageing population sample and lengthened duration of HIV-infection period and extended antiviral therapy over the course of one year. Gomes et al [61] found that, among a large cohort of Hispanic American HIV patients receiving antiviral therapy, significant proportions were either obese or overweight or on their way to developing obesity as well as diabetes mellitus. Reorientations of health care procedures are necessary for patients living with HIV in view of the exaggerated prevalence of overweightness and abdominal obesity linked to sociodemographic and clinical conditions expressed by the consumption of risk foods [62].…”
Section: Volume 1 • Issue 2 • 1000113mentioning
confidence: 99%